Organizational structure and commercialization of coffee and cocoa in the northern amazon region of Ecuador - Viteri Salazar, Oswaldo (2017)
The cultivation of coffee and cocoa is the main source of income for small farmers in the northern Amazon region in Ecuador. As border area, they have been beneficiaries of multiple public and private institutions, principality designed to reactivate the production of coffee and cocoa. The goal was to improve the quality of life of local population threatened by poverty and characterised by high level of immigration from Colombia. The current study was carried out to outline the main obstacles faced by producer associations in order to identify policy measures to address these. This study show data of organisational structure, initiatives for marketing under partnerships, and storage infrastructure with an estimate for the production of coffee and cocoa, based on primary and secondary information. It also implies that the government could play a bigger role supporting peasant organisations in different aspects like: capture of added value by peasants; associative commercialisation with a focus on a popular and solidary economy; and offering flexible credit. All of this would encourage participatory, sustainable rural business ventures. Finally, we present different alternatives for improve the implementation of public agricultural policies, about of organisational structure of the producers, commercialisation processes and environmental concerns.